5.27.13 Problems 1201 to 1300

Table 5.1191: Second order, Linear, non-homogeneous and constant coefficients

#

ODE

Mathematica

Maple

14948

\[ {}y^{\prime \prime }+6 y^{\prime }+8 y = 2 \cos \left (3 t \right ) \]

14949

\[ {}y^{\prime \prime }+6 y^{\prime }+20 y = -3 \sin \left (2 t \right ) \]

14950

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 2 \cos \left (2 t \right ) \]

14951

\[ {}y^{\prime \prime }+3 y^{\prime }+y = \cos \left (3 t \right ) \]

14952

\[ {}y^{\prime \prime }+4 y^{\prime }+20 y = 3+2 \cos \left (2 t \right ) \]

14953

\[ {}y^{\prime \prime }+4 y^{\prime }+20 y = {\mathrm e}^{-t} \cos \left (t \right ) \]

14954

\[ {}y^{\prime \prime }+9 y = \cos \left (t \right ) \]

14955

\[ {}y^{\prime \prime }+9 y = 5 \sin \left (2 t \right ) \]

14956

\[ {}y^{\prime \prime }+4 y = -\cos \left (\frac {t}{2}\right ) \]

14957

\[ {}y^{\prime \prime }+4 y = 3 \cos \left (2 t \right ) \]

14958

\[ {}y^{\prime \prime }+9 y = 2 \cos \left (3 t \right ) \]

14959

\[ {}y^{\prime \prime }+4 y = 8 \]

14960

\[ {}y^{\prime \prime }-4 y = {\mathrm e}^{2 t} \]

14961

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 2 \,{\mathrm e}^{t} \]

14962

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 13 \operatorname {Heaviside}\left (t -4\right ) \]

14963

\[ {}y^{\prime \prime }+4 y = \cos \left (2 t \right ) \]

14964

\[ {}y^{\prime \prime }+3 y = \operatorname {Heaviside}\left (t -4\right ) \cos \left (5 t -20\right ) \]

14965

\[ {}y^{\prime \prime }+4 y^{\prime }+9 y = 20 \operatorname {Heaviside}\left (t -2\right ) \sin \left (t -2\right ) \]

14966

\[ {}y^{\prime \prime }+3 y = \left \{\begin {array}{cc} t & 0\le t <1 \\ 1 & 1\le t \end {array}\right . \]

14967

\[ {}y^{\prime \prime }+3 y = 5 \delta \left (t -2\right ) \]

14968

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = \delta \left (t -3\right ) \]

14969

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = -2 \delta \left (t -2\right ) \]

14970

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = \delta \left (t -1\right )-3 \delta \left (t -4\right ) \]

14971

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = {\mathrm e}^{-2 t} \sin \left (4 t \right ) \]

14972

\[ {}y^{\prime \prime }+y^{\prime }+5 y = \operatorname {Heaviside}\left (t -2\right ) \sin \left (4 t -8\right ) \]

14973

\[ {}y^{\prime \prime }+y^{\prime }+8 y = \left (1-\operatorname {Heaviside}\left (t -4\right )\right ) \cos \left (t -4\right ) \]

14974

\[ {}y^{\prime \prime }+y^{\prime }+3 y = \left (1-\operatorname {Heaviside}\left (t -2\right )\right ) {\mathrm e}^{-\frac {t}{10}+\frac {1}{5}} \sin \left (t -2\right ) \]

14976

\[ {}y^{\prime \prime }+4 y = \sin \left (2 t \right ) \]

14978

\[ {}y^{\prime \prime }+16 y = t \]

14984

\[ {}y^{\prime \prime } = \frac {1+x}{x -1} \]

14987

\[ {}y^{\prime \prime }+3 y^{\prime }+8 y = {\mathrm e}^{-x^{2}} \]

14998

\[ {}y^{\prime \prime } = \sin \left (2 x \right ) \]

14999

\[ {}y^{\prime \prime }-3 = x \]

15212

\[ {}y^{\prime \prime }+2 y^{\prime } = 8 \,{\mathrm e}^{2 x} \]

15221

\[ {}y^{\prime \prime } = 2 y^{\prime }-6 \]

15223

\[ {}y^{\prime \prime }+4 y^{\prime } = 9 \,{\mathrm e}^{-3 x} \]

15241

\[ {}y^{\prime \prime }+4 y^{\prime } = 9 \,{\mathrm e}^{-3 x} \]

15246

\[ {}y^{\prime \prime }+2 y^{\prime } = 8 \,{\mathrm e}^{2 x} \]

15269

\[ {}y^{\prime \prime } = 2 y^{\prime }-5 y+30 \,{\mathrm e}^{3 x} \]

15286

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 9 \,{\mathrm e}^{2 x} \]

15287

\[ {}y^{\prime \prime }-6 y^{\prime }+8 y = {\mathrm e}^{4 x} \]

15411

\[ {}y^{\prime \prime }+4 y = 24 \,{\mathrm e}^{2 x} \]

15412

\[ {}y^{\prime \prime }+4 y = 24 \,{\mathrm e}^{2 x} \]

15413

\[ {}y^{\prime \prime }+2 y^{\prime }-8 y = 8 x^{2}-3 \]

15414

\[ {}y^{\prime \prime }+2 y^{\prime }-8 y = 8 x^{2}-3 \]

15415

\[ {}y^{\prime \prime }-9 y = 36 \]

15416

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -6 \,{\mathrm e}^{4 x} \]

15417

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = 7 \,{\mathrm e}^{5 x} \]

15418

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 169 \sin \left (2 x \right ) \]

15421

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = {\mathrm e}^{4 x} \]

15422

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = {\mathrm e}^{5 x} \]

15423

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -18 \,{\mathrm e}^{4 x}+14 \,{\mathrm e}^{5 x} \]

15424

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = 35 \,{\mathrm e}^{5 x}+12 \,{\mathrm e}^{4 x} \]

15432

\[ {}y^{\prime \prime }+9 y = 52 \,{\mathrm e}^{2 x} \]

15433

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 27 \,{\mathrm e}^{6 x} \]

15434

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = 30 \,{\mathrm e}^{-4 x} \]

15435

\[ {}y^{\prime \prime }+3 y^{\prime } = {\mathrm e}^{\frac {x}{2}} \]

15436

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -5 \,{\mathrm e}^{3 x} \]

15437

\[ {}y^{\prime \prime }+9 y = 10 \cos \left (2 x \right )+15 \sin \left (2 x \right ) \]

15438

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 25 \sin \left (6 x \right ) \]

15439

\[ {}y^{\prime \prime }+3 y^{\prime } = 26 \cos \left (\frac {x}{3}\right )-12 \sin \left (\frac {x}{3}\right ) \]

15440

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = \cos \left (x \right ) \]

15441

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -4 \cos \left (x \right )+7 \sin \left (x \right ) \]

15442

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -200 \]

15443

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = x^{3} \]

15444

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 18 x^{2}+3 x +4 \]

15445

\[ {}y^{\prime \prime }+9 y = 9 x^{4}-9 \]

15446

\[ {}y^{\prime \prime }+9 y = x^{3} \]

15447

\[ {}y^{\prime \prime }+9 y = 25 x \cos \left (2 x \right ) \]

15448

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = \sin \left (x \right ) {\mathrm e}^{2 x} \]

15449

\[ {}y^{\prime \prime }+9 y = 54 x^{2} {\mathrm e}^{3 x} \]

15450

\[ {}y^{\prime \prime } = 6 x \,{\mathrm e}^{x} \sin \left (x \right ) \]

15451

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \left (-6 x -8\right ) \cos \left (2 x \right )+\left (8 x -11\right ) \sin \left (2 x \right ) \]

15452

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \left (12 x -4\right ) {\mathrm e}^{-5 x} \]

15453

\[ {}y^{\prime \prime }+9 y = 39 \,{\mathrm e}^{2 x} x \]

15454

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = -3 \,{\mathrm e}^{-2 x} \]

15455

\[ {}y^{\prime \prime }+4 y^{\prime } = 20 \]

15456

\[ {}y^{\prime \prime }+4 y^{\prime } = x^{2} \]

15457

\[ {}y^{\prime \prime }+9 y = 3 \sin \left (3 x \right ) \]

15458

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 10 \,{\mathrm e}^{3 x} \]

15459

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = \left (72 x^{2}-1\right ) {\mathrm e}^{2 x} \]

15460

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = 4 x \,{\mathrm e}^{6 x} \]

15461

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 6 \,{\mathrm e}^{5 x} \]

15462

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 6 \,{\mathrm e}^{-5 x} \]

15463

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 24 \sin \left (3 x \right ) \]

15464

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 8 \,{\mathrm e}^{-3 x} \]

15465

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = \sin \left (x \right ) {\mathrm e}^{2 x} \]

15466

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = \sin \left (x \right ) {\mathrm e}^{-x} \]

15467

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 100 \]

15468

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = {\mathrm e}^{-x} \]

15469

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 10 x^{2}+4 x +8 \]

15470

\[ {}y^{\prime \prime }+9 y = \sin \left (x \right ) {\mathrm e}^{2 x} \]

15471

\[ {}y^{\prime \prime }+y = 6 \cos \left (x \right )-3 \sin \left (x \right ) \]

15472

\[ {}y^{\prime \prime }+y = 6 \cos \left (2 x \right )-3 \sin \left (2 x \right ) \]

15473

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = x^{3} {\mathrm e}^{-x} \sin \left (x \right ) \]

15474

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = x^{3} {\mathrm e}^{2 x} \sin \left (x \right ) \]

15475

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} {\mathrm e}^{-7 x}+2 \,{\mathrm e}^{-7 x} \]

15476

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} \]

15477

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 4 \,{\mathrm e}^{-8 x} \]

15478

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 4 \,{\mathrm e}^{3 x} \]